An integrated approach using proximity labelling and chemical crosslinking to probe in situ host-virus protein–protein interactions - Jiaqi Li; Zhewang Lin (QRB Discovery)
Host-virus interactions are critically important for various stages of the viral replication cycle. The reliance of viruses on the host factors for their entry, replication, and maturation processes can be exploited for the development of antiviral therapeutics. Thus, the identification and characterization of such viral-host dependency factors has been an attractive area of research to provide novel antiviral targets. Traditional proteomic efforts based on affinity purification of protein complexes from cell lysates are limited to detecting strong and stable interactions. In this perspective, we discuss the integration of two latest proteomic techniques, based on in situ proximity labelling and chemical crosslinking methods, to uncover host-virus protein–protein interactions in living cells.